Transcriptome-wide selection and validation of a solid set of reference genes for gene expression studies in the cephalopod mollusk Octopus vulgaris - Imperadore, Pamela; Cagnin, Stefano; Allegretti, Vittoria; Millino, Caterina; Raffini, Francesca; Fiorito, Graziano; Ponte, Giovanna (Frontiers in Molecular Neuroscience, 2023)
Octopus vulgaris is a cephalopod mollusk and an active marine predator that has been at the center of a number of studies focused on the understanding of neural and biological plasticity. Studies on the machinery involved in e.g., learning and memory, regeneration, and neuromodulation are required to shed light on the conserved and/or unique mechanisms that these animals have evolved. Analysis of gene expression is one of the most essential means to expand our understanding of biological machinery, and the selection of an appropriate set of reference genes is the prerequisite for the quantitative real-time polymerase chain reaction (qRT-PCR). Here we selected 77 candidate reference genes (RGs) from a pool of stable and relatively high-expressed transcripts identified from the full-length transcriptome of O. vulgaris, and we evaluated their expression stabilities in different tissues through geNorm, NormFinder, Bestkeeper, Delta-CT method, and RefFinder. Although various algorithms provided different assemblages of the most stable reference genes for the different kinds of tissues tested here, a comprehensive ranking revealed RGs specific to the nervous system (Ov-RNF7 and Ov-RIOK2) and Ov-EIF2A and Ov-CUL1 across all considered tissues. Furthermore, we validated RGs by assessing the expression profiles of nine target genes (Ov-Naa15, Ov-Ltv1, Ov-CG9286, Ov-EIF3M, Ov-NOB1, Ov-CSDE1, Ov-Abi2, Ov-Homer2, and Ov-Snx20) in different areas of the octopus nervous system (gastric ganglion, as control). Our study allowed us to identify the most extensive set of stable reference genes currently available for the nervous system and appendages of adult O. vulgaris.